2018
DOI: 10.32890/jis2018.14.4
|View full text |Cite
|
Sign up to set email alerts
|

Boko Haram and the Geopolitics of Forced Migration in Nigeria

Abstract: Migration is currently perceived as an epitome of globalization and a measuring gauge of global geopolitical mobility. In recent years, Nigeria has been faced with a series of migratory crises such as insurgency and conflict, forcing large numbers of people to flee from their various residential origins to neighboring countries as refugees and asylum seekers or within their country as Internally Displaced Persons (IDPs). This study explores how geographical and political factors intersects to provide explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Schilling et al (2013) found that the potential of conflict can increase in the receiving area of migrants, especially if the migration is internal, forced and largescale. Such conditions are similar to those present in northeast Nigeria, where large numbers of IDPs migrated within Nigeria as a result of the insurgency of Boko Haram and the counter-insurgency by the state forces (see also IOM, 2016;Mukhtar et al, 2018;Mbiyozo, 2017;Kamta et al, 2020a). It is expected that Africa will most likely experience high impacts of climate change including water scarcity and food security (Niang et al, 2014), with the potential of aggravating conflict, instability and insecurity (Borderon et al, 2019;Scheffran et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Schilling et al (2013) found that the potential of conflict can increase in the receiving area of migrants, especially if the migration is internal, forced and largescale. Such conditions are similar to those present in northeast Nigeria, where large numbers of IDPs migrated within Nigeria as a result of the insurgency of Boko Haram and the counter-insurgency by the state forces (see also IOM, 2016;Mukhtar et al, 2018;Mbiyozo, 2017;Kamta et al, 2020a). It is expected that Africa will most likely experience high impacts of climate change including water scarcity and food security (Niang et al, 2014), with the potential of aggravating conflict, instability and insecurity (Borderon et al, 2019;Scheffran et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…Internal migrant beggars from the Northern areas of Nigeria is not an uncommon feature in Southern part of Nigeria; an earlier study corroborated this ( Salami et al., 2013 ). This has been attributed to many reasons including insecurity resulting from more than a decade long insurgency and other forms of violence in the Northern part of Nigeria ( Mukhtar et al., 2018 ; Kanu et al., 2019 ). Other reasons are poverty which is worse in the Northern part of Nigeria compared to the Southern part ( Kale, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nigeria has been beset with issues on migratory crises such as insurgency and conflict, resulting in large numbers of its people fleeing their homes to neighbouring countries as refugees and asylum seekers or within their country as internally displaced persons (IDPs), (Mukhtar et al, 2018). The Boko Haram insurgency which emerged in 2002 began to use force in 2009 when the leader of the group, Mohammed Yusuf, was killed while in police custody (Emmanuelar, 2015).…”
Section: Introductionmentioning
confidence: 99%